Evaluation of mechanical, thermal and morphological properties of corn husk modified pumice powder reinforced polyester composites. Issue 3 (12th January 2022) - Sari, Nasmi Herlina; Setyawan, Paryanto Dwi; Thiagamani, Senthil Muthu Kumar; Suteja; Tamimi, Roby; Rangappa, Sanjay Mavinkere; Siengchin, Suchart
Abstract: Researchers are continuously working to improve the mechanical characteristics of polymer composites by various approaches such as fiber treatment, filler addition, and others. In this study, mechanical, thermal, and morphological characteristics of composites produced from corn husk waste fibers treated with pumice powder were examined. Corn husk (CHF) and pumice powder (SBA) were mixed in polyester matrix at varied volume fractions of 5:30, 10:25, 15:20, 20:15, 25:10, and 30:5. The results demonstrate that infusing SBA into the CHF composite enhanced the interfacial adhesion between the CHF and the polyester matrix. As a result, the mechanical and thermal characteristics of the SBA/CHF composites were significantly improved. The composite with 5:30 volume fraction (JPA) exhibited the highest values of tensile strength (18.61 MPa), tensile modulus (3.23 GPa), flexural strength (36.12 MPa), and flexural modulus (3.39 GPa) among all the composites and the polymer matrix which was attributed to the strong SBA/CHF interface bonds in the composites. While the lowest values recorded for the composite specimens were due to a large number of CHF pullouts. Similarly, JPA composites outperformed the other composites in terms of thermal stability. The morphological study indicated that CHF pullout increased with an increased quantity of CHF and dropped as the amount of SBA increased and was distributed equally in the composite. According to the findings, the CHF/SBA composites had better mechanical characteristics than the fiber‐glass composites.